High prevalence of carbapenem-resistant Pseudomonas aeruginosa and identification of a novel VIM-type metallo-β-lactamase, VIM-92, in clinical isolates from northern China - Zhao, Linbo; Pu, Jiekun; Liu, Yunning; Cai, Heng; Han, Meijuan; Yu, Yunsong; Tang, Jianhua (Frontiers in Microbiology, 2025)
Carbapenem-resistant Pseudomonas aeruginosa (CRPA) has become a serious global health concern due to the limited treatment options. The primary resistance mechanism in CRPA involves the production of metallo-β-lactamases (MBLs), making MBL-producing P. aeruginosa a significant component of CRPA cases. To understand the prevalence of CRPA in hospitals in northern China, we conducted a preliminary screening and identification of CRPA in 143 clinical isolates of P. aeruginosa collected from various departments of a tertiary hospital between 2021 and 2023, analyzing CRPA resistance trends in certain regions of northern China during this period. We identified 71 CRPA isolates that exhibited high carbapenem resistance and phylogenetic tree analysis revealed that ST244 CRPA isolates had widely spread across various departments of the same hospital over three consecutive years. We also identified two VIM-producing isolates, PJK40 and PJK43, both of which carried the same novel VIM-type metallo-β-lactamase, VIM-92, encoded by a newly identified gene, blaVIM-92, closely related to blaVIM-24. blaVIM-92 was embedded in class 1 integrons within the Tn1403 transposon. The blaVIM-92-carrying plasmid, pPJK40, was found to resemble the pJB37 megaplasmid. The expression of VIM-92 and VIM-24 in DH5α and PAO1 revealed similar effects of the MICs of β-lactams, except for aztreonam. The high prevalence of CRPA in clinical settings, and the identification of VIM-92, highlights the urgent need for ongoing surveillance of CRPA and emerging MBL variants in P. aeruginosa.